Minimal Invasive Diagnostic Capabilities and Effectiveness of CFRP-Patches Repairs in Long-Term Operated Metals - Lesiuk, Grzegorz; Pedrosa, Bruno A. S.; Zięty, Anna; Błażejewski, Wojciech; Correia, Jose A. F. O.; De Jesus, Abilio M. P.; Fragassa, Cristiano (Metals (Basel ), 2020)
The paper deals with the subject of diagnostics and the quick repairs of long-term operated metallic materials. Special attention was paid to historical materials, where the structure (e.g., puddle iron) is different from modern structural steels. In such materials, the processes of microstructural degradation occur as a result of several decades of exposure, which could overpass 100 years. In some cases, their intensity can be potentially catastrophic. For this reason, the search for minimally invasive diagnostic methods is ongoing. In this paper, corrosion and fracture toughness tests were conducted, and the results of these studies were presented for two material states: post-operated and normalized (as a state “restoring” virgin state). Moreover, through the use of modern numerical methods, composite crack-resistant patches have been designed to reduce the stress intensity factors under cyclic loads. As a result, fatigue lifetime was extended (propagation phase) by more than 300%.